2002
DOI: 10.2527/2002.8071925x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of bovine germinal cells into mouse testes

Abstract: To develop techniques for spermatogonial transplantation in bulls, it is essential to have an effective bioassay procedure to evaluate the transplantation efficiency of spermatogonial stem cell collection, purification, and culture techniques. The objective of the present study was to develop a mouse bioassay model to evaluate transplantation efficiency of fresh and cultured bovine germ cells. Bull calves of four ages (1, 2, 3, and 4 mo) were used as a source of donor testes cells. Two calves were used for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 13 publications
2
35
0
1
Order By: Relevance
“…Currently, methods for efficiently culturing and transplanting SSCs are only available for rodents (Brinster & Avarback 1994, Brinster & Zimmermann 1994 and have yet to be fully established for livestock species, though some initial progress has been made (Dobrinski et al 2000, Izadyar et al 2003, Oatley et al 2002, 2004b, Aponte et al 2008. Development of these procedures in rodents has been aided greatly by identification of surface markers expressed by undifferentiated spermatogonia, allowing for isolation of cell fractions enriched for these cells compared to the total testis cell population.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, methods for efficiently culturing and transplanting SSCs are only available for rodents (Brinster & Avarback 1994, Brinster & Zimmermann 1994 and have yet to be fully established for livestock species, though some initial progress has been made (Dobrinski et al 2000, Izadyar et al 2003, Oatley et al 2002, 2004b, Aponte et al 2008. Development of these procedures in rodents has been aided greatly by identification of surface markers expressed by undifferentiated spermatogonia, allowing for isolation of cell fractions enriched for these cells compared to the total testis cell population.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine SSCs were successfully cultured on a monolayer of STO (SIM 6-thioguanine resistant ouabain resistant) feeder cells [24], bovine embryonic fibroblast cells (BEF) [25] and Sertoli cells [26]. Bovine SSCs were also cultured for short term on laminin coated plates in vitro [11].…”
Section: Introductionmentioning
confidence: 99%
“…The spectacular discoveries impel scientists to investigate the potential of SSCs from large animals in this respect. As reported, SSCs from domestic species could colonize and proliferate in host mouse testes after transplantation, but could not give rise to entire spermatogenesis , Izadyar et al 2002, Oatley et al 2002, Kim et al 2006; Table 2), probably due to the phylogenetic disparity between donors and hosts. Later, allogeneic transplantation of SSCs was tested in boars, bulls, goats, sheep, and dogs (Honaramooz et al 2002a, Izadyar et al 2003, Herrid et al 2006, 2009b, Kim et al 2008, and the development of the donor germ cells was observed in those recipients of homogeneous species ( Fig.…”
Section: Transplantation Of Sscs From Domestic Animalsmentioning
confidence: 84%